2018
DOI: 10.5194/bg-15-6909-2018
|View full text |Cite
|
Sign up to set email alerts
|

Leaf area index identified as a major source of variability in modeled CO<sub>2</sub> fertilization

Abstract: Abstract. The concentration–carbon feedback (β), also called the CO2 fertilization effect, is a key unknown in climate–carbon-cycle projections. A better understanding of model mechanisms that govern terrestrial ecosystem responses to elevated CO2 is urgently needed to enable a more accurate prediction of future terrestrial carbon sink. We conducted C-only, carbon–nitrogen (C–N) and carbon–nitrogen–phosphorus (C–N–P) simulations of the Community Atmosphere Biosphere Land Exchange model (CABLE) from 1901 to 210… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 94 publications
(113 reference statements)
6
22
0
1
Order By: Relevance
“…As atmospheric CO 2 concentration increases, carboxylation is stimulated. This biochemical stimulation is scaled up through a biological hierarchy that progresses from leaf photosynthesis to canopy GPP, vegetation NPP, and to net changes in the carbon-pool sizes of plants and soil 3 . Across those scales, the carboxylation stimulation is amplified by some processes, but diminished by others.…”
mentioning
confidence: 99%
“…As atmospheric CO 2 concentration increases, carboxylation is stimulated. This biochemical stimulation is scaled up through a biological hierarchy that progresses from leaf photosynthesis to canopy GPP, vegetation NPP, and to net changes in the carbon-pool sizes of plants and soil 3 . Across those scales, the carboxylation stimulation is amplified by some processes, but diminished by others.…”
mentioning
confidence: 99%
“…Also, the TRENDY2 models simulated the relative increases in global LAI of 10.2–20.7% per 100 ppm (Zhu et al, 2016). The effect of CO 2 fertilization on LAI varied with location, vegetation type, and soil nutrient condition (Li et al, 2018). Our study indicates that the largest CO 2 fertilization effect on LAI occurs at low latitudes, with an averaged value of 27.5% per 100 ppm, and the weakest response to elevated CO 2 occurs at middle‐high latitudes, with the average coefficient being 6.2% per 100 ppm, as a result of the strong temperature dependence of the photosynthetic response on elevated CO 2 (Girardin et al, 2016; Hickler et al, 2008; Schimel et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The CO 2 stimulation of carboxylation then translates into increased gross primary production (GPP) and net primary production (NPP), leading to increased carbon allocation to leaves and hence increased LAI. LAI is identified as a major source of variability in modeled CO 2 fertilization (Li et al, 2018), and the effect of CO 2 fertilization on LAI has been identified as a major uncertainty in modeling the response of the terrestrial carbon cycle to global climate change (Huntzinger et al, 2017). However, the effects of elevated CO 2 concentrations on plant growth (McMurtrie et al, 2008) are poorly understood, and as a consequence, the models differ widely in their prognostications (Huntzinger et al, 2017; Tian et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Indirect effects of eCO 2 , including soil water savings due to reduced stomatal conductivity, stimulation of the canopy leaf area (LA) development and faster soil nutrient depletion, are assumed to partially explain discrepancies in eCO 2 effects between leaf and whole‐tree levels (Fatichi et al, 2016). Absence of a straightforward translation from the leaf to the whole‐tree level (Steppe, Sterck, & Deslauriers, 2015), especially under eCO 2 conditions, hinders the prediction of a general tree response to climate change based on leaf level observations (Fatichi et al, 2016; Q. Li, Lu, et al, 2018; Paschalis et al, 2017; Wullschleger et al, 2002).…”
Section: Introductionmentioning
confidence: 99%